FAKTOR-FAKTOR YANG MEMPENGARUHI PENINGKATAN CAKUPAN IMUNISASI CAMPAK DI WILAYAH KERJA PUSKESMAS BLANG MANGAT KOTA LHOKSEUMAWE - Jalil, Subki Abdul; Mauyah, Nizan; Syahabuddin, Syahabuddin (Indonesian Trust Health Journal, 2024)
Measles is a very contagious disease. Measles is an important cause of death in children throughout the world. Pre-school and elementary school children are vulnerable to contracting measles. Measles is caused by viruses from the genus Morbillivirus and belongs to the Paramyxovirus group. Measles is also called morbilli or measles. Measles is transmitted through air contaminated with droplets from the nose, mouth or throat of an infected person. In 2020, the spread of suspected measles cases occurred in almost all provinces of Indonesia. There were 3,382 suspected measles cases, a decrease compared to 2019, namely 8,819 cases. The highest number of suspected measles cases were in the provinces of Central Java (680 cases), DKI Jakarta (596 cases), and DI Yogyakarta (408 cases), West Java (323 cases) and Aceh (233 cases). (Kemenkes RI, 2021). This study aims to analyze the relationship between maternal characteristics and information sources with measles immunization. The respondents were 62 mothers who visited the Blang Mangat Community Health Center, Blang Mangat District, Lhokseumawe City using the Accidental Sampling technique. Data were collected using a questionnaire and analyzed using the Chi Square Test and Fisher's Exact Test at α = 5%. The results showed that the factors age (p=0.306), occupation (p=0.116), income (p=1,000) and information from electronic media (p=0.515) had no relationship with measles immunization. Meanwhile, factors related to measles immunization were education (p=0.043) and information from health workers (p=0.018). It is recommended that: 1) The public provide complete immunization for children to avoid infectious diseases, especially measles. 2) Community leaders and religious leaders (Ustadz) are expected to convey to the public to provide support and information about measles immunization. 3) At the Blang Mangat Community Health Center, efforts need to be made to provide effective and continuous information such as health education, distributing posters, distributing leaflets and putting up banners about measles immunization. Abstrak Derajat kesehatan masyarakat suatu negara dipengaruhi oleh keberadaan sarana kesehatan. Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan menyatakan bahwa fasilitas pelayanan kesehatan adalah suatu alat dan/atau tempat yang digunakan untuk menyelenggarakan upaya pelayanan kesehatan, baik promotif, preventif, kuratif, maupun rehabilitatif yang dilakukan oleh pemerintah pusat, pemerintah daerah, dan/atau masyarakat. Penelitian ini bertujuan untuk menganalisis hubungan karakteristik ibu dan sumber informasi dengan pemberian imunisasi campak. Responden adalah ibu-ibu yang berkunjung ke Puskesmas Blang Mangat Kecamatan Blang Mangat Kota Lhokseumawe sebanyak 62 orang dengan teknik Accidental Sampling. Pengumpulan data dengan menggunakan kuesioner dan dianalisis menggunakan Uji Chi Square dan Uji Exact Fisher pada α =5%. Hasil penelitian menunjukkan bahwa faktor umur (p=0,306), pekerjaan (p=0,116), penghasilan (p=1,000) dan informasi dari media elektronik (p=0,515) tidak ada hubungan dengan pemberian imunisasi campak. Sedangkan faktor yang berhubungan dengan pemberian imunisasi campak adalah pendidikan (p=0,043) dan informasi dari petugas kesehatan (p=0,018). Disarankan kepada: 1) Kepada masyarakat untuk memberikan imunisasi lengkap pada anak agar terhindar dari penyakit menular terutama penyakit campak. 2) Kepada tokoh masyarakat dan tokoh agama (Ustadz) diharapkan menyampaikan kepada masyarakat untuk memberikan dukungan dan informasi tentang imunisasi campak. 3) Kepada Puskesmas Syamtalira Blang Mangat perlu dilakukan upaya penyampaian informasi yang efektif dan berkesinambungan seperti penyuluhan kesehatan, membagikan poster, membagikan leaflet dan memasang spanduk tentang imunisasi campak.